Open Source Software: Lessons from and for Software Engineering. - Fitzgerald, Brian (Computer (00189162), 2011)
Despite initial suggestions to the contrary, open source software projects exhibit many of the fundamental tenets of software engineering. Likewise, the existence of category-killer apps suggests that conventional software engineering can draw some lessons from OSS.